Emerging Mechanisms of Physical Exercise Benefits in Adjuvant and Neoadjuvant Cancer Immunotherapy - Fabio Casciano; Lorenzo Caruso; Enrico Zauli; Arianna Gonelli; Giorgio Zauli; Mauro Vaccarezza (Biomedicines)
The primary factors that can be modified in one’s lifestyle are the most influential determinants and significant preventable causes of various types of cancer. Exercise has demonstrated numerous advantages in preventing cancer and aiding in its treatment. However, the precise mechanisms behind these effects are still not fully understood. To contribute to our comprehension of exercise’s impact on cancer immunotherapy and provide recommendations for future research in exercise oncology, we will examine the roles and underlying mechanisms of exercise on immune cells. In addition to reducing the likelihood of developing cancer, exercise can also improve the effectiveness of certain approved anticancer treatments, such as targeted therapy, immunotherapy, and radiotherapy. Exercise is a pivotal modulator of the immune response, and thus, it can play an emerging important role in new immunotherapies. The mechanisms responsible for these effects involve the regulation of intra-tumoral angiogenesis, myokines, adipokines, their associated pathways, cancer metabolism, and anticancer immunity. Our review assesses the potential of physical exercise as an adjuvant/neoadjuvant tool, reducing the burden of cancer relapse, and analyzes emerging molecular mechanisms predicting favorable adjuvanticity effects.